The role of environmental and technology policies in the transition to a low-carbon energy industry - Christoph Heinzel; Ralph Winkler (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
In a dynamic general equilibrium model we study the interplay between gradual and structural change in the transition to a low-carbon energy industry. We focus on the welfare-theoretic consequences of diverging social and private rates of time preference and a time-to-build feature in capital accumulation. Both features are particularly important in the transformation of energy systems. We show that only a combination of environmental and technology policies can achieve a socially optimal transition. We thus provide a new reason for environmental regulation to be complemented by technology policy such as a non-distortionary investment subsidy.
Keywords: H23; Q48; H43; 330; environmental and technology policy; social vs. individual rates of time preference; time to build; gradual vs. structural technological change; energy industry; Umweltpolitik; Technologiepolitik; Strukturwandel; Elektrizitätswirtschaft; Technischer Fortschritt; Intertemporale Entscheidung; Wirkungsanalyse; Dynamisches Gleichgewicht; Theorie